HYBRIDMINDS—summary and outlook of the 2023 international conference on the ethics and regulation of intelligent neuroprostheses - Buthut, Maria; Starke, Georg; Akmazoglu, Tugba Basaran; Colucci, Annalisa; Vermehren, Mareike; van Beinum, Amanda; Bublitz, Christoph; Chandler, Jennifer; Ienca, Marcello; Soekadar, Surjo R. (Frontiers in Human Neuroscience, 2024)
Neurotechnology and Artificial Intelligence (AI) have developed rapidly in recent years with an increasing number of applications and AI-enabled devices that are about to enter the market.While promising to substantially improve quality of life across various severe medical conditions, there are also concerns that the convergence of these technologies, e.g., in the form of intelligent neuroprostheses, may have undesirable consequences and compromise cognitive liberty, mental integrity, or mental privacy. Therefore, various international organizations, such as the Organization for Economic Cooperation and Development (OECD) or United Nations Educational, Scientific and Cultural Organization (UNESCO), have formed initiatives to tackle such questions and develop recommendations that mitigate risks while fostering innovation. In this context, a first international conference on the ethics and regulation of intelligent neuroprostheses was held in Berlin, Germany, in autumn 2023. The conference gathered leading experts in neuroscience, engineering, ethics, law, philosophy as well as representatives of industry, policy making and the media. Here, we summarize the highlights of the conference, underline the areas in which a broad consensus was found among participants, and provide an outlook on future challenges in development, deployment, and regulation of intelligent neuroprostheses.